GESTÃO DE RESÍDUOS NA PRODUÇÃO INDUSTRIAL DE BIODIESEL - Ferreira, Kerlen Jacqueline Nunes (2014)
The search for alternative energy sources has been stimulated, due to the concern to reduce the high levels of pollution and dependence on fossil fuels. For this reason, the use of biofuel is being increasingly exploited as is the case of biodiesel sources which are renewable. It can be produced from vegetable oil, residual and animal fat, among others. However, a concern related to the biodiesel industry are the waste from production. This study aims to verify the processes of industrial production of biodiesel, identify and characterize the waste resulting from extraction steps / refining of soybean oil and the transesterification process, and measure the most significant waste for the industry, with the aim of proposing waste management plan PGR. The methodology adopted in this study was exploratory type, which is characterized by the search for more information about a subject and Descriptive type where the data obtained in the survey should be analyzed and interpreted, either qualitatively or quantitatively. This study contributed information necessary for the biodiesel sector, through the identification of waste production, as well as adoption of proactive measures, through the management of waste based on the principles of Cleaner Production.